INAPPROPRIATE BEHAVIOURS IN MAINLAND PUBLIC AND PRIVATE PRIMARY SCHOOLS OF LAGOS STATE, NIGERIA: NEED FOR COUNSELLING SERVICES - John O. Oparaduru; Augustine C. Ukwueze (Indonesian Journal of Learning and Instruction)
This study examined inappropriate behaviours in public and private primary schools across Mainland Area of Lagos State, Nigeria using a survey research design. The population of the study comprised all the pupils in both public and primary schools in Mainland Area of Lagos State. Through random sampling from randomly selected schools in Lagos Mainland, 53 male and 95 female respondents were respectively selected for the study. An Instrument called Childhood Misbehaviour Inventory was constructed and validated to obtain the data used for the study. Research questions were answered using descriptive statistics (mean and standard deviation) while the hypotheses were tested at 0.05 level of significance using t-test statistics. It was found that inappropriate behaviours in mainland schools among pupils are bullying, lateness, not paying attention in the class, hatred for teachers, noise making, truancy, walking out of the class during lesson without permission, and sleeping in class. The study also revealed that these inappropriate behaviours in primary schools are as a result of lateness to class by teachers, child abuse, and poor parenting styles, peer influence, sibling rivalry, poverty, unconducive environment and poor parental care among others. The study recommends that counselling should be introduced and made compulsory for all primary schools in Lagos Mainland as a panacea to incessant cases of inappropriate behaviours among the pupils in primary schools so as to catch them young to exhibit appropriate behaviours. Keywords: inappropriate behaviours; students; public schools; private schools; counselling services.